Dealing with distributional effects of flood risk management in China: compensation mechanisms in flood retention areas. Issue 5 (4th July 2019) - Dai, L.; van Doorn-Hoekveld, W. J.; Wang, R. Y.; van Rijswick, H. F. M. W.
ABSTRACT: One of China's flood protection strategies is to create flood retention areas. This article focuses on how China deals with the infringements of property use rights caused by the creation and use of flood retention areas. It describes the legal framework of flood retention areas, the associated compensation mechanisms and other mechanisms that may be used in the future to offset the adverse consequences of the rights of individuals in flood retention areas.